2021
DOI: 10.1136/bmjspcare-2020-002830
|View full text |Cite
|
Sign up to set email alerts
|

Serious Illness Conversations in advanced kidney disease: a mixed-methods implementation study

Abstract: ObjectiveAdvanced kidney disease is associated with a high risk of morbidity and mortality. Consequently, invasive treatments such as dialysis may not yield survival benefits. Advance care planning has been encouraged. However, whether such discussions are acceptable when done earlier, before end-stage kidney treatment decision-making occurs, is unclear. This pilot study aimed to explore whether use of the Serious Illness Conversation Guide to aid early advance care planning is acceptable, and to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Of these, 11 were randomized controlled trials (RCTs) using different methods, 28–30,47,53,55,60,61,63,64,66 1 was a secondary analysis of data from an RCT, 65 and 2 studies also had an experimental design but were not RCTs 43,51 . Seven studies had a prospective study design, 41,42,46,48,49,56,68 3 studies were intervention development and piloting studies, 44,45,69 1 study was a mixed methods implementation study, 67 3 studies were retrospective observational studies, 40,57,59 1 study was an economic evaluation based on data from one of the retrospective studies, 58 1 was a cross-sectional study with a pre- and post-test survey, 50 1 was an evaluation of the procedure of a multidisciplinary deliberation clinic through an Ethics Committee in Nephrology, 54 1 was a case review and guide for nephrologists, 52 and 1 was a qualitative interview study with thematic analysis 62 . Patient involvement interventions were mostly evaluated in clinical settings 28–30,40–45,47–51,53–55,57–67 or simulation centers 46,56,68,69 .…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 11 were randomized controlled trials (RCTs) using different methods, 28–30,47,53,55,60,61,63,64,66 1 was a secondary analysis of data from an RCT, 65 and 2 studies also had an experimental design but were not RCTs 43,51 . Seven studies had a prospective study design, 41,42,46,48,49,56,68 3 studies were intervention development and piloting studies, 44,45,69 1 study was a mixed methods implementation study, 67 3 studies were retrospective observational studies, 40,57,59 1 study was an economic evaluation based on data from one of the retrospective studies, 58 1 was a cross-sectional study with a pre- and post-test survey, 50 1 was an evaluation of the procedure of a multidisciplinary deliberation clinic through an Ethics Committee in Nephrology, 54 1 was a case review and guide for nephrologists, 52 and 1 was a qualitative interview study with thematic analysis 62 . Patient involvement interventions were mostly evaluated in clinical settings 28–30,40–45,47–51,53–55,57–67 or simulation centers 46,56,68,69 .…”
Section: Resultsmentioning
confidence: 99%
“…One barrier for implementation was the physicians' fear of taking away patients' hope when talking about what might happen. However, a recent study showed that patients felt SIC helped them to reflect on their prognosis and goals of care, and did not decrease their hope or provoke anxiety [41]. Another study described that the conversations were useful, and although they did not find any differences in patients' experiences of peacefulness or hopefulness, they found that the patients experienced better planning for future care with a focus on their personal priorities [22].…”
Section: Discussionmentioning
confidence: 97%
“… Staff = 14 10 (71.4%) The shifts in processes employed by inter-professional clinicians revealed comprehensive models for prognostic communication and creative workflows to ensure that patients with complex illnesses had proactive, longitudinal, and patient-centered SICs and care planning. Thamcharoen et al (2021) [ 54 ] U.S. This pilot study aimed to explore whether use of the SICG to aid early ACP is acceptable, and to evaluate the information gained from these conversations. Mixed-methods implementation study.…”
Section: Table A1mentioning
confidence: 99%